2009
DOI: 10.1055/s-0029-1218286
|View full text |Cite
|
Sign up to set email alerts
|

A New Way to Generate Functionalized Bridges in [2,2]Cyclophanes

Abstract: The synthesis of valuable precursors of cyclic endiynes has been accomplished by base-catalyzed intramolecular cyclization of pinacolone-type compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Since the discover y of the metallic conductivity in a tetrathiafulvalene-tetracyanoquinodimethane complex [2] tetrachalcogenafulvalenes have played a leading role in the development of new molecular metals and superconductors [3][4][5]. In general, charge-transfer [6][7][8][9][10][11][12] or push-pull [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compounds have important applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [30][31][32][33][34][35][36][37][38][39] and not only (biologically active compounds, daily life and even the educational process) [40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…Since the discover y of the metallic conductivity in a tetrathiafulvalene-tetracyanoquinodimethane complex [2] tetrachalcogenafulvalenes have played a leading role in the development of new molecular metals and superconductors [3][4][5]. In general, charge-transfer [6][7][8][9][10][11][12] or push-pull [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compounds have important applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [30][31][32][33][34][35][36][37][38][39] and not only (biologically active compounds, daily life and even the educational process) [40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…In this context, a variety of acceptor units have been investigated, nitrogen and sulfur containing cations receiving a great deal of attention [9][10][11][12][13][14][15][16][17][18][19]. Of special interest for conducting materials are charge-transfer [20][21][22][23][24][25][26][27][28][29][30] and push-pull [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] compounds. Recent studies on (1,3-dithiolium-2yl)phenolates systems revealed that 1,3-dithiolium cations can act as acceptor groups in intramolecular chargetransfer processes [27,30,48,49].…”
mentioning
confidence: 99%
“…daily life and even the educational process) [18][19][20][21][22][23][24][25][26][27][28][29]. Charge-transfer [30][31][32][33][34][35][36][37][38][39][40][41] or push-pull [42][43][44][45][46][47][48][49][50][51][52][53][54][55] compounds have important applications in the field of conducting materials. An important precursor for 1,3-dithiol-2-ylidene derivatives are the 1,3-dithiolium-2-yl compounds [56,57].…”
mentioning
confidence: 99%